REVIEW. Issue 2 (8th December 2011) - Sassu, Gianluigi
PHILOSOPHICAL APPROACHES TO COMMUNICATION, CLAUDE MANGION, (2011) first edition, Bristol and Chicago: Intellect, 330 pp, ISBN 978-1-84150-429-2, paperback £19.95/$40